(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
The article presents research devoted to theoretical and methodological issues of determining the solvency of business entities, the economic content of the concepts of solvency and creditworthiness, the relationship of solvency with other economic indicators and the conclusions drawn on their basis.